THE EFFECTIVENESS OF INDIVIDUAL EDUCATION PLANS AND HOW THEY SUPPORT CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN SCHOOLS - Bamuhaise, Flora-Marie (2016)
This study examines the effectiveness of IEPs in supporting children with Special Education Needs in schools. Theoretical perspectives from constructivists such as Jean Piaget and Lev Vygotsky have been considered throughout the document in the various discussions. The literature review discusses the role of the IEP in various countries and the controversial issues that have emerged overtime about the effectiveness of the IEP. The methodological approach which has been applied in this study is adopted from the social science researchers where a theoretical and interpretivist lens in used to discuss issues that emerge from various studies. The implications for practice have been discussed in relation Vygotsky’s theories where he emphasises the issue of the Zone of Proximal development and Scaffolding.